2012
DOI: 10.1007/s10040-011-0819-x
|View full text |Cite
|
Sign up to set email alerts
|

Review: Some low-frequency electrical methods for subsurface characterization and monitoring in hydrogeology

Abstract: Low-frequency geoelectrical methods include mainly self-potential, resistivity, and induced polarization techniques, which have potential in many environmental and hydrogeological applications. They provide complementary information to each other and to in-situ measurements. The self-potential method is a passive measurement of the electrical response associated with the in-situ generation of electrical current due to the flow of pore water in porous media, a salinity gradient, and/or the concentration of redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
189
1
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 283 publications
(221 citation statements)
references
References 245 publications
(254 reference statements)
2
189
1
9
Order By: Relevance
“…The bulk electrical conductivity (σ b ) includes contributions from the electrical conductivity of pore water and the surface conduction at the pore and water-mineral interface (Revil et al, 2012). We employed the model proposed by Linde et al (2006), which was extended from Archie's model (Archie, 1942), and is expressed below as…”
Section: Petrophysical Modelmentioning
confidence: 99%
“…The bulk electrical conductivity (σ b ) includes contributions from the electrical conductivity of pore water and the surface conduction at the pore and water-mineral interface (Revil et al, 2012). We employed the model proposed by Linde et al (2006), which was extended from Archie's model (Archie, 1942), and is expressed below as…”
Section: Petrophysical Modelmentioning
confidence: 99%
“…The average of the inversion RMS (root mean square) is about 19.3%, which is due chiefly to the field noises from pumping activities and using the 2D inversion scheme for the 3D objects. Factors that can generate noisy measurements in pumping environments include induction in the ground associated with power lines, direct current injection associated with cathodic grounding (Corwin and Hoover 1979), and the metallic casing of a piezometer (Revil et al 2012). These factors are the possible sources that contribute to noisy measurements and higher RMS in the inversion.…”
Section: The Monitoring Configurations For Time-lapse Resistivitymentioning
confidence: 99%
“…Electrical resistivity tomography (ERT) has proven its efficiency to image and/or monitor spatial phenomena [43] such as salt water intrusions [44,45], variations in moisture content (e.g., [46,47]), biodegradation of hydrocarbons (e.g., [48,49]) and salt tracer experiments (e.g., [50,51] and references therein). An in-depth review of electrical properties of rocks can be found in Schön [52] or Revil et al [53], whereas a description of electrical methods can be found in Binley and Kemna [54]. The panel seems slightly heterogeneous and reflects lithological changes.…”
Section: Electrical Resistivity Tomographymentioning
confidence: 99%